Pemberdayaan Masyarakat Dalam Upaya Pencegahan Dan Penanganan Anemia Pada Ibu Hamil Di Puskesmas Pembantu Bandar Klippa Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Tahun 2022 - Lasria Yolivia Aruan; Yasrida Nadeak; Ika Damayanti Sipayung; Plora S (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Anemia in pregnant women can be a cause of postpartum hemorrhage and an indirect cause of death. Community involvement as a community where anemia clients live in pregnant women is of course very much needed in an effort to provide social support for anemia clients in pregnant women. The purpose of this activity is to empower the community in an effort to prevent and treat anemia in pregnant women at the Bandar Klippa auxiliary health center. The method of implementing this Community Service Program is a form of partnership with health center cadres and officers, training health cadres and counseling about anemia in pregnant women at the Bandar Klippa Assistant Health Center, Percut Sei Tuan District, Deli Tengah Regency, which is one of the inspirational efforts for PPM (Community Service Program) activities. , where the number of participants who attended the first stage of the training were 36 cadres, 10 students, 1 village head and 1 health center officer and 12 pregnant women, while in stage II the number of cadres who attended was 38 people and 1 assistant head of the health center as Resource Person. Activities start from the stages of planning, implementation, evaluation to the preparation of reports.